Catalogue of central stars of extragalactic planetary nebulae - Weidmann, Walter Alfredo (2025)
Context. Central stars of planetary nebulae (CSPNe) are essential for understanding the final evolutionary stages of low- andintermediate-mass stars. However, their study in extragalactic environments remains challenging due to their intrinsic faintness andthe limited availability of high-quality data.Aims. We aim to provide a comprehensive and up-to-date catalogue of extragalactic CSPNe in order to enable a more complete viewof their physical properties across different galactic environments and metallicities.Methods. The catalogue was assembled using data from the most recent and reliable literature sources. Priority was given to collectingeffective temperatures and luminosities that have either been directly reported or consistently derived. When available, spectral typesor specific spectral features – such as P-Cygni profiles or broad Hα emission lines – were also included. This approach allowed forbroader characterisation of the sample, even when accurate classifications are not available.Results. We present a new compilation of extragalactic CSPNe – the largest to date – comprising over 1000 objects located in theMagellanic Clouds, NGC 300, NGC 5128, and fifteen other nearby galaxies. This catalogue enables, for the first time, a globalcomparison of CSPNe physical parameters beyond the Milky Way. Updated Hertzsprung–Russell diagrams are provided featuringCSPNe from seven different galaxies, revealing trends and outliers that merit further investigation. The catalogue represents a valuableresource for future spectroscopic follow-up and for improving our understanding of post-AGB evolution in diverse galactic contexts.